Adrenal function and high dose inhaled corticosteroids for asthma - Milner, Anthony D.; Conway, Elvira; Honour, John W.; Yiallouros, Panayiotis K. (My University, 1997)
Objective—To investigate eVects on adrenal function of fluticasone, a recently released inhaled steroid preparation with lower systemic bioavailability than beclomethasone dipropionate. Methods—34 children on high doses (400- 909 µg/m2 /d) of inhaled beclomethasone dipropionate or budesonide were recruited into a double blind, crossover study investigating the eVects on adrenal function of beclomethasone and fluticasone propionate, given using a standard spacer (Volumatic). The 24 hour excretion rates of total cortisol and cortisol metabolites were determined at baseline (after a two week run in), after six weeks treatment with an equal dose of beclomethasone, and after six weeks of treatment with half the dose of fluticasone, both given through a spacer device. Results—The comparison of eVects between fluticasone and beclomethasone during treatment periods, although favouring fluticasone in all measured variables, reached significance only after correction for urinary creatinine excretion (tetrahydrocortisol and 5á-tetrahydrocortisol geometric means: 424 v 341 µg/m2 /d). The baseline data showed adrenal suppression in the children taking beclomethasone (total cortisol geometric means: 975 v 1542 µg/d) and a dose related suppression in the children taking budesonide. Suppressed adrenal function in the children who were taking beclomethasone at baseline subsequently improved with fluticasone and beclomethasone during treatment periods. Conclusions—Fluticasone is less likely to suppress adrenal function than beclomethasone at therapeutically equivalent doses. The baseline data also support the claim that spacer devices should be used for the administration of high doses of inhaled topical steroids
Keywords: Inhaled corticosteroids; Adrenal function; Spacer devices